2002
DOI: 10.1523/jneurosci.22-03-00815.2002
|View full text |Cite
|
Sign up to set email alerts
|

N-myc Promotes Survival and Induces S-Phase Entry of Postmitotic Sympathetic Neurons

Abstract: In most postmitotic neurons, expression or activation of proteins that stimulate cell cycle progression or DNA replication results in apoptosis. One potential exception to this generalization is neuroblastoma (NB), a tumor derived from the sympathoadrenal lineage. NBs often express high levels of N-myc, a proto-oncogene that can potently activate key components of the cell cycle machinery. Here, we show that in postmitotic sympathetic neurons, N-myc can induce S-phase entry while protecting neurons from death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 54 publications
1
66
0
Order By: Relevance
“…37,38 Importantly, we showed that this effect was transient in the perinatal period and correlated with increased Bmi1 mRNA expression, compared with mature postnatal cells. Moreover, Bmi1 mRNA expression was induced by MycN in a stepwise manner during tumorigenesis, consistent with a recent study showing that MycN induced Bmi1 transcription.…”
Section: Discussionmentioning
confidence: 74%
“…37,38 Importantly, we showed that this effect was transient in the perinatal period and correlated with increased Bmi1 mRNA expression, compared with mature postnatal cells. Moreover, Bmi1 mRNA expression was induced by MycN in a stepwise manner during tumorigenesis, consistent with a recent study showing that MycN induced Bmi1 transcription.…”
Section: Discussionmentioning
confidence: 74%
“…Other studies have indirectly shown a relation of MYCN with cell cycle regulation. Over-expression of MYCN in quiescent cells accelerates S-phase progression after mitogenic stimulation, while silencing of MYCN by RNAi causes a decrease of cells in S-phase (Wartiovaara et al, 2002;Woo et al, 2008). Direct MYCN transcriptional target genes in cell cycle regulation however have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is interesting to compare the role of the cell-cycle machinery in apoptosis of neurons in the CNS and peripheral nervous system (PNS). A recent study revealed distinct responses of CNS and PNS neurons to expression of the transcription factor N-myc that promotes cell-cycle progression in dividing cells (Wartiovaara et al, 2002). Whereas N-myc induced successful re-entry of sympathetic neurons into the cell cycle, N-myc induced apoptosis of cortical neurons (Wartiovaara et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed distinct responses of CNS and PNS neurons to expression of the transcription factor N-myc that promotes cell-cycle progression in dividing cells (Wartiovaara et al, 2002). Whereas N-myc induced successful re-entry of sympathetic neurons into the cell cycle, N-myc induced apoptosis of cortical neurons (Wartiovaara et al, 2002). It will be interesting to compare the cell-cycle protein responses of PNS and CNS neurons to activity deprivation.…”
Section: Discussionmentioning
confidence: 99%